Introducing criteria and indicators for monitoring and auditing forest management in the Brazilian Amazon - Pokorny B.; Sabogal, C.; Prabhu, Ravi; Silva, J.N.M. (CIFOR and Embrapa Amazonia Oriental, 2002)
The development of criteria and indicators (C&I) for good forest management was identified as one of the essential components of a research and demonstration project in the Brazilian Amazon under the leadership of Embrapa Eastern Amazon and CIFOR. Four steps were envisaged: (1) Definition of a preliminary list of regionally adapted C&I during an international expert workshop; (2) Evaluation and refinement of this list by four key stakeholder groups (researchers, government officials, managers, and local actors); (3) Development of monitoring and auditing prototypes based on the assessment results, and (4) Validation of the defined instruments through supervised application in different forest enterprises and auditing entities. As part of this process, a field-test of a preliminary list of C&I by stakeholder group confirmed the high practicability of C&I based control activities as well as the need and potential of participatory methods in the development process. Further analysis confirmed that practical work on C&I systems will have to focus more at the verifiers level. Social and ecological verifiers need to be more specific and practicable methods for their assessing will have to be developed. To ensure an effective interpretation of monitoring and auditing results it is recommended to structure the C&I in four categories: existence and quality of documentation, efficient implementation plans, impact of enterprise activities, and external conditions for sustainability.